Performance improvement of inductive coupling system using ferrite materials. (2021) - Swain, Biswaranjan; Halder, Jayshree; Swain, Nibedita; Nayak, P.P.; Bhuyan, S.
Abstract: Ferrite Encumbered inductive coupling-based energy transmission is interestingly being investigated both theoretically and experimentally as an alternative technique of delivering power through human skin and body for wireless excitation of implantable electronic devices. In the explored system, to enhance the efficiency, the magnetic flux produced by the transmitting coil can be improved focused through the ferrite loaded printed receiving coil by cautious symmetrical placement of ferrite materials. The properties of ferrites include high magnetic permeability and high electrical resistance. In this paper, a ferrite configuration is estimated using Finite Element Method, and an efficient model is nominated for construction and laboratory testing. The proposed technique entails an energy transfer efficiency of ∼48.2% at maximum output power of 248 mW and resonant frequency of 120 kHz over a separation gap of 3 cm. The real-time body temperature of human has been recorded through the energized temperature sensor and corroborated with a calibrated system which ensures the precision of the developed prototype system. The real time data collected in the laboratory are in good agreement with the simulation results, which specify that the laboratory physical prototype and circuit closely followed to the physical and electrical parameters of the simulation. The ferrite loaded resonant inductive coupling technique is considered as a feasible and supportive substitute to the conventional technique for implantable electronic sensors.